Faktor-Faktor yang Mempengaruhi Performa Automatic Teller Machine (ATM) pada Bank Syariah Mandiri Cabang Tenggarong Seberang - Mainata, Dedy (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2019)
Automatic Teller Machine (ATM) is a machine that can serve the needs of customers automatically at any time (24 hours) and 7 days a week including holidays. Location ATMs in strategic places. Efforts to improve the bank's fee-based income (FBI) also reflected the addition of machines ATM as one source of FBI of banks. Problems often seen on ATM in Islamic banks is service excellent. ATM location selection is one of the things that can affect the performance of the ATM. ATM placements in strategic locations that do not will have an impact on the quantity of the ATM transactions. The purpose of this study to find out what are the factors that affect the performance of ATM and the dominant factor affecting the performance of ATM at the Bank Syariah Mandiri branch Tenggarong Seberang. This type of research is descriptive qualitative research sample is purposive sampling. Factors affecting the performance of ATM at the Bank Syariah Mandiri branch Tenggarong Seberang is a potential FBI, service excellent and marketing strategies. The dominant factor affecting the performance of ATM at the Bank Syariah Mandiri branch Tenggarong Seberang is service excellent. Tenggarong Seberang local community character is not so concerned related to cleanliness and speed of service. The most important thing is the availability of money at an ATM, however cleanliness, convenience and speed of transaction is part of the services should still be maintained BSM Tenggarong Seberang branch.